Correlational research on college students’ physical exercise behavior, academic engagement, and self-efficacy - Gao, Wei; Chen, Jiaxin; Tu, Zhi; Li, Ming (Frontiers in Psychology, 2025)
ObjectiveThis study aims to investigate the current status of physical exercise behavior, academic engagement, and self-efficacy among non-physical education college students. Additionally, it sought to analyze the relationships between these factors in order to explore the potential impact of physical exercise on learning and self-efficacy.MethodsTo examine the current status and relationships between physical exercise behavior, academic engagement, and self-efficacy, this study used the Physical Activity Rating Scale (PARS-3), the Utrecht Work Engagement Scale (UWES), and the General Self-Efficacy Scale (GESE) as research tools. A stratified random sampling method was employed, and non-physical education college students were selected as participants. A total of 1,596 valid questionnaires were analyzed. The data were processed using SPSS 26.0, AMOS 26.0, and Excel 2010, with statistical analyses including one-way ANOVA, correlation analysis, regression analysis, and mediation effect testing.ResultsPhysical exercise behavior among non-physical education students showed significant positive correlations with academic engagement (r = 0.207, p < 0.01) and self-efficacy (r = 0.218, p < 0.01). Academic engagement was also strongly positively correlated with self-efficacy (r = 0.811, p < 0.01). The partial mediating effect of physical exercise on academic engagement was significant, with the mediation ratio of ab/c = 84.7%.ConclusionPhysical exercise behavior significantly predicts academic engagement, and a positive predictive relationship exists between physical exercise and self-efficacy. Additionally, self-efficacy plays a significant role in predicting academic engagement. Self-efficacy partially mediates the relationship between physical exercise behavior and academic engagement.